Sistem Informasi Pembenihan Kentang Pada Balai Benih Induk (BBI) Kabupaten Kerinci - Sundara, Tri A; Yulia, Yulia (Universitas Andalas, 2017)
The development of computer technology in Indonesia is currently growing rapidly. In line with this the development of the Potato Seed Center (BBI) of potatoes was also developing, as was the case at the Kerinci Regency mother's seed plant. Processing of potato hatchery and hatchery development reports has not been computerized because it still uses Microsoft Excel, causing some problems including making reports on the development of potato hatcheries and searching for data takes quite a long time. This led to a weak processing of hatchery data processing systems and the development of reports on the development of Kerinci Regency potato seeding. Seeing the above problems, a potato seeding information system at the Central Seed Agency (BBI) was made using a C # programming language that had used a database and used Crytal Report to assist in the development of a report on the development of potato seedlings in the potato seed plant in Kerinci district.